Using Herringbone Technique to Improve the Reading Comprehension Ability of the Students of SMU Bhakti Ibu 1 Palembang - Roma Nur Asnita (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2013)
Abstract: This study was conducted to find out whether there was a significant difference between reading comprehension ability of students who were taught by using Herringbone technique and those who were taught by using the traditional approach. The method used was experimental method.  The instrument for collecting the data was a reading comprehension test.  It was given to subjects before and after the experiment.  The subjects chosen for this study were 40 second year students of SMU Bhakti Ibu 1 Palembang.  They were divided into two groups : experimental  and control group. Based on the findings, the results of t-test and interpretations, the following conclusions were drawn : (1) Herringbone technique was applicable to improve students’ ability in reading comprehension, and (2) there was a significant difference between reading comprehension ability of students who were taught by using Herringbone technique and those who were taught by using the traditional approach.  It was evidenced by the calculation of t-test. Keywords : herringbone technique, reading comprehension ability